Long-term survival of LGR5 expressing supporting cells after severe ototoxic trauma in the adult mouse cochlea - Smith-Cortinez, Natalia; Hendriksen, Ferry G. J.; Ramekers, Dyan; Stokroos, Robert J.; Versnel, Huib; Straatman, Louise V. (Frontiers in Cellular Neuroscience, 2023)
The leucine-rich repeat-containing G-protein coupled receptor 5 (LGR5) is a tissue resident stem cell marker, which it is expressed in supporting cells (SCs) in the organ of Corti in the mammalian inner ear. These LGR5+ SCs can be used as an endogenous source of progenitor cells for regeneration of hair cells to treat hearing loss and deafness. We have recently reported that LGR5+ SCs survive one week after ototoxic trauma. Here, we evaluated Lgr5 expression in the adult cochlea and long-term survival of LGR5+ SCs following severe hearing loss. Lgr5GFP transgenic mice and wild type mice aged postnatal day 30 (P30) and P200 were used. P30 animals were deafened with a single dose of furosemide and kanamycin. Seven and twenty-eight days after deafening, auditory brainstem responses (ABRs) were recorded. Cochleas were harvested to characterize mature hair cells and LGR5+ SCs by immunofluorescence microscopy and quantitative reverse transcription PCR (q-RT-PCR). There were no significant age-related changes in Lgr5 expression when comparing normalhearing mice aged P200 with P30. Seven and twenty-eight days after ototoxic trauma, there was severe outer hair cell loss and LGR5 was expressed in the third row of Deiters' cells and in inner pillar cells. Seven days after induction of ototoxic trauma there was an up-regulation of the mRNA expression of Lgr5 compared to the normal-hearing condition; twenty-eight days after ototoxic trauma Lgr5 expression was similar to normal-hearing levels. The presence of LGR5+ SCs in the adult mouse cochlea, which persists after severe hair cell loss, suggests potential regenerative capacity of endogenous cochlear progenitor cells in adulthood. To our knowledge, this is the first study showing not only long-term survival of LGR5+ SCs in the normal and ototoxically-damaged cochlea, but also increased Lgr5 expression in the adult mouse cochlea after deafening, suggesting long-term availability of potential target cells for future regenerative therapies.